2013
DOI: 10.1532/hsf98.2013160
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes following Alemtuzumab Induction in Lung Transplantation

Abstract: Alemtuzumab induction with reduced immunosuppression offers a comparable 5-year survival and rejection rate compared to standard-dose immunosuppression regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The rationale for induction immunosuppression in lung transplantation is based on outcomes from previous studies in other solid organ transplantation. To date, studies of induction immunosuppression in lung transplantation have been either small or retrospective in nature and although there are conflicting results, there are trends suggesting that induction agents decrease the incidence of acute rejection and provide improvements in long-term outcomes without a significant increase in infectious complications or adverse side effects (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The most convincing data showing benefits of induction immunosuppression come from two large, retrospective studies using the ISHLT and United Network for Organ Sharing (UNOS) registry databases.…”
Section: Induction Immunosuppressionmentioning
confidence: 99%
“…The rationale for induction immunosuppression in lung transplantation is based on outcomes from previous studies in other solid organ transplantation. To date, studies of induction immunosuppression in lung transplantation have been either small or retrospective in nature and although there are conflicting results, there are trends suggesting that induction agents decrease the incidence of acute rejection and provide improvements in long-term outcomes without a significant increase in infectious complications or adverse side effects (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The most convincing data showing benefits of induction immunosuppression come from two large, retrospective studies using the ISHLT and United Network for Organ Sharing (UNOS) registry databases.…”
Section: Induction Immunosuppressionmentioning
confidence: 99%
“…Alemtuzumab is a monoclonal lymphocyte-depleting agent that acts through binding of CD52 on the cell surface of B and T cells, monocytes, macrophages and natural killer cells (9,13). In a study of Wehman et al alemtuzumab induction with reduced immunosuppression showed a comparable rate of AR and overall survival in comparison to conventional immunosuppression with corticosteroids, a calcineurin inhibitor and a cytostatic agent (23). In addition, Shyu et al could demonstrate an improved freedom from AR and lymphocytic bronchiolitis and a prolonged CR-free survival in LTx patients induced with alemtuzumab in comparison to LTx patients induced with ATG, daclizumab or conventional immunosuppression.…”
Section: Lymphocyte-depleting Agents: Atg Okt3 Alemtuzumabmentioning
confidence: 99%
“…However, the absolute risk of fatal cardiac arrhythmia is low and in fact comparable to that of alternative antibiotics (76). Azithromycin may be considered the safest of all macrolides since serum levels in healthy volunteers are >3,000 times lower than drug concentrations required for cardiomyocyte potassium channel (hERG/IKr)blockade, action potential prolongation and QTc prolongation (22)(23)(24). Caution is nevertheless required for toxic accumulation of azithromycin in patients with impaired hepatic function, in case of concomitant use of other QT-prolonging drugs, or underlying structural heart disease.…”
Section: Azithromycinmentioning
confidence: 99%
“…CD52 is also expressed in comparatively smaller amounts on macrophages, monocytes, and eosinophils 10,11 ; thus, changes in the count of these cell types are also possible. Alemtuzumab has been proven to be safe and useful in the prevention of acute rejection, 12 also improving bronchiolitis‐obliterans syndrome‐free survival, 13 while infective complication possibilities are similar to those following the standard immunosuppressive regimen 14 …”
Section: Introductionmentioning
confidence: 99%
“…Alemtuzumab has been proven to be safe and useful in the prevention of acute rejection, 12 also improving bronchiolitis-obliterans syndrome-free survival, 13 while infective complication possibilities are similar to those following the standard immunosuppressive regimen. 14 As-to our knowledge-no data have been published on peripheral blood mononuclear cells (PBMC) and BALIC profiles after alemtuzumab induction therapy. In this study, the time course and the possible differences compared to ATG induction were examined.…”
Section: Introductionmentioning
confidence: 99%